Gaucher disease: molecular screening of the glucocerebrosidase 1601G and 1601A alleles in Victoria, British Columbia, Canada. - Choy, F Y (1997)
Gaucher disease is the most prevalent lysosomal storage disease and it results from inherited deficient glucocerebrosidase activity. The glucocerebrosidase gene from normal people was sequenced by several laboratories and it was noted that a G or A nucleotide may be present at cDNA position 1601, resulting in 495arginine or 495histidine in the glucocerebrosidase polypeptide. In order to rule out the possibility of cloning error and to elucidate the genetic status of the two genotypes and their distribution in the population, we have developed a convenient and reliable method for the molecular screening of the 1601G and 1601A genotypes in the population. This method uses PCR amplification of glucocerebrosidase genomic DNA in blood samples, followed by BsaHI restriction fragment length polymorphism analysis. Out of the 256 subjects without Gaucher disease and 15 Gaucher patients surveyed, the 1601G genotype was present in the homozygous form in all of the asymptomatic subjects and 14 Gaucher patients. In one Gaucher patient who was diagnosed as having type 1 (non-neuropathic) Gaucher disease with the A1226G/T1366G mutations, the heterozygous 1601G/A genotype was detected. These findings indicate that the 1601G genotype which encodes 495arginine of the glucocerebrosidase polypeptide is not a cloning error. Instead, it constitutes the normal as well as predominant genotype in the population in the municipality of Greater Victoria, British Columbia. The 1601A genotype, on the other hand, appears to be quite infrequent in this population. The availability of our restriction enzyme based method has allowed the screening and frequency determination of these two alleles in other populations.